Ascidians from Rocas Atoll, northeast Brazil - Paiva, Sandra V.; Oliveira Filho, Ronaldo R. de; Lotufo, Tito M. da Cruz (Frontiers in Marine Science, 2015)
Rocas Atoll is the only one of its kind in the South Atlantic—and the first Brazilian marine biological reserve. This is the first report about the ascidians from Rocas. A total of 12 species were found, 5 of them not hitherto described: Ascidia viridina sp. nov., Didemnum rochai sp. nov., Leptoclinides crocotulus sp. nov., Polysyncraton maurizeliae sp. nov., and Trididemnum rocasensis sp. nov.). One Caribbean species, Didemnum halimedae, was also discovered in the region for the first time. Further, this is the first record of Didemnum digestum in the Atlantic. The results indicate a high degree of endemism in the ascidian fauna from Rocas Atoll, where didemnids are presently the most important members.